(untitled) (American Journal of Islam and Society, 1994)
The collapse of the Soviet Union, which resulted in the demise of the fonner bipolar system in international relations, has led writers to offer predictions about the future framework of international political relationships. Francis Fukuyama posits the end of history as a result of the end of the cold war. Samuel Hlllltington speculates that the post-cold war world will be divided according to differences in civilizations: a "clash of civilizations." Unlike Hwttington, Mark Juergensmeyer argues that any future conflict will have a religious nature. Hwttington predicts that the struggle will occur on the international level, whereas Juergensmeyer says it will take place on the nation-state level, for religious nationalism will challenge the dominant secular ideology that now rules nation-states. Before proceeding, two important elements asserted by Juergensmeyer should be kept in mind: the conflict between secular nationalism and religious nationalism will take place in the Third World and will be confined to the borders of the nation-state. In other words, Islamic movements will not be united and their concern will be limited to their respective cmmtries. Based on these assertions, we can assume that the West wiH remain secular and unthreatened by religious revolts, and that the conflict may develop from the national to the international level (i.e., between western secular states and nonwestem nation-states dominated by religious groups). The book is based on interviews conducted by the author with leaders of various religious groups and an analysis of their writings. Muslim, Hindu, Buddhist, Sikh, and Jewish movements are studied. In the first chapter, "The Loss of Faith in Secular Nationalism," the author examines the emergence of nationalism in the Third World through the works of Hans Kohn and Donald Smith. The main theme here is the religious rejection of secular nationalism. He asserts that secular nationalists are perceived by religious nationalists as partners in a western-led global conspiracy against religion: An example occurred in 1991 during the Gulf War: Islamic political groups in Egypt reversed their initial condemnation of Iraq’s invasion of Kuwait when the United States sent thousands of ...